Rare malformation of glans penis: Arteriovenous malformation - Akin, Y.; Sarac, M.; Yucel, S. (Medknow Publications & Media Pvt Ltd, 2013)
Pediatric glans penis malformations, especially arteriovenous malformations (AVM), are very rare. Herein, we report two rare cases. A 14-year-old boy attended our outpatient clinic with chief complaints of purple swelling and rapidly growing lesion on the glans penis. The lesion was excised surgically after physical and radiological evaluations. Pathology reported AVM and the patient is being followed up. The second case is a 2-year-old boy who was admitted with a big lesion involving glans penis and genital area that has been present since birth. In physical and radiological evaluations, lesion on the glans penis was pulsatile. Parents of the patient did not want any surgery and patient has been in follow-up. Diagnosis of the vascular lesions on glans penis is very easy by physical and radiological examinations today. Long-term follow-up is very important for AVM. Clinicians must make a careful effort to document new glans lesions in the pediatric population and decrease anxiety in the parents of affected children.
Keywords: Arteriovenous malformations; glans penis; penis anomalies